KEWENANGAN PENYELESIAN SENGKETA KONSUMEN PERJANJIAN KREDIT MOTOR DALAM PERPEKTIF HUKUM - Suyikati (Faculty of Law, University of Dr. Soetomo, 2021)
The issue of forced motorcycle withdrawals by leasing companies is of particular concern to regulations that have not yet provided a solution to these problems, considering that the application of standard agreements has its own weaknesses, consumer issues handled by BPSK regarding motorcycle withdrawals by leasing parties, resulting in consumers losing control over motorcycles but BPSK does not have a big role in carrying out legal actions and its authority is still limited and its decisions still do not have executorial legal force, seeing this many phenomena the Constitutional Court issued Constitutional Court Decision No.18/PUU-XVII/2019 this decision gives a lot perceptions about the procedure for withdrawing vehicles that are fiduciary guarantees, one of which is the right to execute through the courts, but execution without trial is allowed on the condition that the debtor acknowledges a default. This means that the Court only examines article 15 paragraph 2 while the Obj The guarantee certificate has actually been transferred unilaterally, meaning that it is legal for the creditor to make a withdrawal with reference to the contents of the main agreement between the creditor and the debtor and article 1338 of the Civil Code. Keywords: Authority. Dispute, motorbikes, Law